Urban climate data for Gothenburg, 1983-2020 - Rayner, David; Lindberg, Fredrik; Kukulies, Julia; Thorsson, Sofia; Wallenberg, Nils (University of Gothenburg, 2021)
This dataset contains time-series of hourly climate constructed by merging records from various meteorological stations in and near Gothenburg, Sweden.

The variables included are:
- Central European Time (UTC+1)
- Air temperature (degC).
- Average wind speed (m/s)
- Average wind direction (deg true)
- Relative humidity (%)
- Global radiation (short-wave radiation down on a horizontal surface, W/m/m).
- Diffuse radiation (diffuse short-wave radiation down on a horizontal surface, W/m/m).
- Mean sea-level pressure (hPa).
- Direct-beam short wave radiation (W/m/m) incident on a plane normal to the solar angle.

The dataset covers the period 1986-09-01 - 2020-12-31.

Data files are provided in .csv and NetCDF format (https://www.unidata.ucar.edu/software/netcdf/)

Further details are provided in the file README_utf8.txt.

Change to metadata.
Detta dataset innehåller timvisa klimattidsserier konstruerade genom att kombinera data från meteorologiska stationer i och nära Göteborg, Sverige.

De inkluderade variablerna är:
- Centraleuropeisk tid (UTC+1)
- Lufttemperatur (degC).
- Genomsnittlig vindhastighet (m/s)
- Genomsnittlig vindriktning (deg true)
- Relativ luftfuktighet (%)
- Global strålning (kortvågig strålning på en horisontell yta, W/m/m).
- Diffus strålning (diffus kortvågsstrålning på en horisontell yta, W/m/m).
- Havsnivåstryck (hPa).
- Direktstrålande kortvågig strålning (W/m/m) på ett plan som är normalt till solvinkeln.

Datasetet täcker perioden 1986-09-01 - 2020-12-31.

Datafiler finns i .csv- och NetCDF-format (https://www.unidata.ucar.edu/software/netcdf/).

Ytterligare information finns i filen README_utf8.txt.
Urbana klimatdata för Göteborg, 1983-2020
Keywords: air temperature; lufttemperatur; air relative humidity; solar radiation; solstrålning; wind direction; diffuse solar radiation intensity; atmospheric pressure; Atmospheric conditions; Atmosfäriska förhållanden; wind speed; Physical Geography; Naturgeografi; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Geoscientific Information; Geovetenskap; Climatology / Meteorology / Atmosphere; Klimatologi och meteorologi